The Development of Education Statistics Digital Scrapbook Integrated with Problem-Based Learning at Universitas Terbuka - Tri Dyah Prastiti; Dafik Dafik; Jackson P Mairing; Sri Tresnaningsih (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2021)
One of the learning characteristics applied by Universitas Terbuka (UT) is using digital media integrated with problem-based learning in independent learning. This research was intended to develop digital scrapbooks as the digital media integrated with problem-based learning to foster the students’ learning outcomes in Statistics Education. As many as 108 UT students who took Statistics Education subject in the 2020 registration period were targeted as the research subjects; they involved 56 students participating in webinar tutorials and 52 students participating in online tutorials. The research instruments used were the assessment sheets used by the experts, the student questionnaires, and tests. There were five stages of developmental research as applied in this research, and they covered planning, exploratory studies, product development, expert validation, and field testing in small groups. The results obtained were that the digital scrapbook met the expert validity based on the constructivism theory and statistical concepts. Moreover, the implementation of digital scrapbooks met practical criteria since all students felt enthusiastic and claimed that it was able to help them in understanding Statistics Education. Its implementation met the effective criteria based on the mean scores obtained on the student learning outcomes, 75.75 on the 0-100 scale, and no students scored under 60. It was concluded that the use of digital scrapbooks in the Statistics Education subject met validity, practical, and effective criteria.